PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS ADOBE FLASH MENGGUNAKAN KONTEKS RUMAH WANITA KOTA LUBUKLINGGAU DITINJAU DARI SEGI KEVALIDAN DAN KEPRAKTISAN - Ririn Suhariani; Rani Refianti; Lucy Asri Purwasi (LP4MK STKIP PGRI Lubuklinggau, 2021)
This study aims to develop interactive learning media based on adobe flash by using the context of the Women's House Lubuklinggau City on valid and practical trigonometry material. This research is a development research using the ADDIE model (Analysis, Design, Development, Implementation and Evaluation). The subjects of this study include validators (language, material and media experts), mathematics teachers and class X students in the one to one and small group test. The data collection technique was carried out using a questionnaire sheet. Based on the results of the analysis of the validation questionnaire assessment by the three validators, it shows that the learning media developed meets the very valid criteria with a validity result of 81.45%. While the results of the analysis of the practicality questionnaire assessment by teachers and students showed that the learning media developed met the very practical criteria with practicality results of 95.31%.